The observation and simulation of the airpiane flutter on low band television broadcasting signal - Wonggeeratigun, A.; Sangonchat, P.; Noppanakeepong, S.; Leelaruji, N.; Moriya, Y. (My University, 2003)
The paper studies effect of quasi-periodic or airplane flutter pheiiomcnon on television broadcasting. Airplane flutter is a very important problem. It causes the receiving antenna to receive both direct signal by the Tx (Transmitter antenna) and reflected signa1 scattered by the airplane with phase delay. The sum of two signals results in fading, sometime coilapse and distortion of picture on TV screen. W e performed measurement and modeling this phenomenon on TV signal when the airplane flew across and the range Tx and Rx (Receiver antenna). The frequency 60.75MHz (Aural frequency of CH3) is used under tests. A single scatter multipath model is introduced. It is used to duplicate some of the measured data and show the dependence of power variation on the airplane fluttering. Tlie fluctuation of the airplane flutter phenomenon was calculated to be around 2-4dB.
Keywords: Airplane flutter; Interference on TV signal; Quasi-periodic